SURGICAL TECHNIQUE FOR ANATOMICAL RE-CONSTRUCTION OF THE DISTAL RADIOULNAR LIGAMENTS IN CHRONIC TRAUMATIC INJURY OF THE TRIANGULAR FIBROCARTILAGE COMPLEX - Nikola Simeonov; Kalin Angelov; Iliyana Marcheva; Elena Apostolu; Мargarita Kateva (Journal of the Bulgarian Orthopaedics and Trauma Association)
Abstract-Injury to the triangular fibrocartilage complex (TFCC) can lead to instability of the distal radioulnar joint (DRUJ). In this article, we have presented a treatment method for patients with chronic traumatic TFCC injury. The surgical technique described here demonstrates anatomical reconstruction of the volar and dorsal distal radioulnar ligament using an autologous palmaris longus tendon graft.In the period 2014-2023, 22 patients with chronic traumatic injury to the triangular fibrocartilage complex, leading to instability of the DRUJ, were operated on in our clinic. The main parameters studied pre- and post-operatively were: degree of pain during active movements in the wrist joint and prono-supination of the forearm,range of active movements in the same joints, stability of DRUJ and grip strength relative to the contralateral limb.All 22 patients reported pain reduction with active wrist movements and forearm prono-supination.   This surgical  technique with anatomically based reconstruction of the distal volar and dorsal radioulnar ligament provides restoration of stability of the distal radioulnar joint and reduction of pain in patients with chronic injury to the triangular fibrocartilage complex.